Effect of single or combined caffeine and L-Theanine supplementation on shooting and cognitive performance in elite curling athletes: a double-blind, placebo-controlled study - Yilmaza, U.; Buzdagli, Y.; Polatc, M. L.; Bakirc, Y.; Ozhancic, B.; Alkazanc, S.; Ucard, H. (Journal of the International Society of Sports Nutrition, 2023)
Purpose: Previous studies have investigated the effect of single or combined caffeine (CAF) and L-theanine (THE) intake on attention performance. However, its effect on shooting performance and cognitive performance in a sport is unknown. The aim of this study was to investigate the hypothesis "Does single or combined CAF and THE supplementation have an effect on shooting and cognitive performance in elite curling athletes?." It is predicted that over the next decade, studies based on nutritional ergogenic supplements in the deveoping sport of curling will continue to increase, leading to a significant increase in studies examining the effects of CAF and THE supplementation, alone or in combination, on throwing and cognitive performance in elite curling athletes.